Desenvolvimento de indicadores de vulnerabilidade à seca na região semiárida brasileira - Rosendo, Eliamin Eldan Queiroz (2014)
The Brazilian Northeast has been characterized from the beginning of its history, the stigma of periodic droughts, however most research on the topic of drought are usually developed with our gaze fixed on the physical aspects such as the severity, extent, frequency, are often neglecting the social, economic, cultural and productive aspects of the region. Given the importance of analyzing the climatic factors together with studies of existing vulnerabilities in the Brazilian semiarid region. This study aimed to show the vulnerability to drought in the municipalities of Picuí, Sumé and Sousa, respectively, located in the regions of Seridó Ocidental paraibano, Cariri Oriental paraibano and Sertão of the state of Paraíba. This was done by means of an adaptation of indicators Bhattacharya and Dass (2007), which deal with the vulnerability, and their factors of exposure, sensitivity and adaptive capacity, using data mainly from the municipalities in the year 2010 in government agencies and non-governmental, official websites on the internet and through fieldwork. It was concluded by analyzing the results of Picuí that the municipality had the highest exposure, with an index of 0.39043 and worse performance sensitivity, with the index of 0.2515. Regarding the indicator Adaptive Capacity of the municipality Sume was the one that stood out negatively, getting the index of 0.3155. In general terms the municipality of Picuí showed the greatest vulnerability (0.3467), followed by the municipality of Sume (0.2973) and the municipality of Sousa (0.2876) Indicators of Exposure, Sensitivity and Adaptive Capacity is shown to be useful tools for the analysis of the intrinsic characteristics of drought, population characteristics, production activities and the way that they are practiced. About Vulnerability Index, it was set up as a suitable for the study of holistic risk management to environmental disasters instrument that can be used for the formulation of public policies for managers and decision makers and can assist the development of plans local preparedness, mitigation and coexistence of drought weather